Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 264033 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Pitangus sulphuratus (Linnaeus, 1766)", "TaxonKey is Psittacula krameri (Scopoli, 1769)" ] }, "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 264033 records from 215 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0072814-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences